Changes in the distribution of American family incomes, 1947 to 1984 - Levy, Frank (1987)
The American family income distribution now lies at the center of several controversies. Some observers argue that the American middle class is vanishing, but U.S. census income statistics show income inequality has not changed appreciably since 1947. A second controversy involves whether average living standards have risen or fallen since the major oil price increase of 1973-74. These controversies can be partially resolved by understanding the sharp slowdown in the growth of workers' wages which occurred after 1973 and the demographic trends which kept per capita living standards rising despite stagnant wages, including more working women and low birthrates.